Tandem couples counseling : an innovative approach to working with high conflict couples - Levitov, Justin E.; Fall, Kevin A. (New York, NY : Routledge, 2021)
This book introduces the protocol known as Tandem Couples Counseling (TCC), a ground-breaking model that provides sound theoretical explanations and interventions that address the inherent difficulties in traditional forms of couples counseling. Tandem Couples Counseling: An Innovative Approach to Working with High Conflict Couples synthesizes the research literature from the fields of couples counseling and group work into a compelling therapeutic approach. Extensive case examples illuminate the dynamics and skills of the approach. Assessment processes and rich descriptions of the treatment protocols are included, enabling integration, and understanding of how to implement this approach with clients as well as immediately work to improve the connection in existing co-therapy arrangements. The text is an essential guide for counseling professionals on how to build, maintain, and use the co-therapy relationship as an agent of change for high-conflict couples.
1. A Brief History of Couples Counseling and the Evolution of Tandem Couples Counseling -- 2. Defining and Assessing High Conflict Couples -- 3. Philosophical Basis for a Tandem Couples Counseling Approach -- 4. Co-Therapy: Rationale and Effective Application -- 5. Tandem Couples Counseling Protocol -- 6. Tandem Couples Counseling with Other Dyads: The Adult Child-Parent Client -- 7. Consultation and Supervision Within Tandem Couples Counseling.
OCLC-licensed vendor bibliographic record.
Keywords: Couples therapy; PSYCHOLOGY / Psychotherapy / Couples & Family; PSYCHOLOGY / Psychotherapy / Counseling